Quality of Sleep and Blood Glucose of Type 2 Diabetes Mellitus - Alwi, Fahrizal; Leli Herawati; Hizrah Hanim Lubis; Mersi Ekaputri; Razyda Hayati (International Journal of Public Health Excellence (IJPHE), 2023)
Diabetes Mellitus is a serious problem with a rapidly increasing incidence. Almost all groups of people around the world are attacked by this disease. High blood sugar levels interfere with concentration to sleep well, due to the frequent urge to urinate at night and excessive thirst. The study was to determine the relationship between the quality of sleep and blood glucose levels in patients with type 2 diabetes mellitus. The study was a descriptive correlative with a cross-sectional approach. Seventy-seven respondents were involved in this study and were selected by accidental sampling. Data were collected using The Pittsburgh Sleep Quality Index to determine the quality of sleep and blood glucose levels were measured using Nesco Multicheck. Data were analyzed using chi-square. The results showed that there was a significant relationship between the quality of sleep and blood glucose levels with a p-value of 0.001. It can be concluded that the quality of sleep is related to the patient's blood glucose levels, so it is very important for patients to keep going with good quality of quality.